Evaluation of soybean genotypes for high temperature tolerance during reproductive stages: Evaluation of soybean genotypes for high temperature tolerance during reproductive stages - SUBHASH CHANDRA; GIRIRAJ KUMAWAT; GYANESH K SATPUTE; V S BHATIA; SANJAY GUPTA; DIPENDRA SINGH; RUCHA K; V NATARAJ; M B RATNAPARKHE; V RAJESH; M SHIVAKUMAR; HUKUM SINGH (Journal of Oilseeds Research, 2023)
High temperature is one of the major abiotic factors restricting plant growth and development. In this investigation, twenty soybean accessions were evaluated for different morpho-physiological and yield traits at two different day/night temperatures (30°C/20°C & 40°C/28°C) under green house conditions in year 2018-19 and 2019- 20 where high temperature stress was induced at onset of reproductive stage to till the maturity of the crop. Same panel of genotypes was also evaluated for delayed leaf senescence and related traits during summer 2019 and summer 2020. The experimental results revealed that genotypes NRC 146, 6A-58-5 and JS 20-98 performed better consistently in high temperature conditions while genotypes ICS 84/86-85B-4, JS 95-60, JS 90-41 were found to be highly sensitive.